'How can experience of local residents be "knowledge"?' Challenges in interdisciplinary climate change research. Issue 1 (19th April 2015) - Yeh, Emily T
Abstract : Despite widespread acceptance of the idea of working across disciplines and methods in climate change research, the interpretive social sciences continue to be relatively neglected in interdisciplinary research endeavours. Much greater appreciation across epistemological differences is necessary for inclusive collaborative efforts, which in turn requires explicit discussion of what those differences are. Based on the author's participation in an interdisciplinary research project on climate change in Tibet, this article discusses three conceptual challenges: knowledge, system and ontology.